PELATIHAN MANAJEMEN ANGGARAN DAN PERENCANAAN KEUANGAN RUMAH TANGGA MENUJU KELUARGA SEJAHTERA DI KELURAHAN CENGKARENG TIMUR - Rahmatullah Rahmatullah; I Nyoman Suri Adnyana; Didi Sukardi; Murdiyono Murdiyono (Nusantara Hasana Journal, 2024)
This community service activity aims to increase public understanding, particularly among housewives in the East Cengkareng sub-district, regarding the importance of budget management and family financial planning. A common problem faced by the community is the lack of ability to manage income and expenses, which leads to household economic instability. This activity was carried out through lectures and question-and-answer discussions involving local residents as participants. The material provided included preparing a household budget, managing expenses based on a priority scale, the importance of saving, and planning an emergency fund. The results of the activity showed that participants gained an increased understanding of managing family finances effectively and efficiently. In addition, participants also began to understand the importance of simple financial record-keeping as a first step towards a more prosperous and financially independent family.